Mapeamento do uso e cobertura da terra no assentamento Jacaré-Curituba, se com o uso da imagem de alta resolução espacial - Lima, Luana Brito (2020)
The research was carried out in the rural settlement of Jacaré-Curituba, which houses an irrigated perimeter and is inserted in the territory of two municipalities: Canindé de São Francisco and Poço Redondo, in the semi-arid region of Sergipe, both located on the banks of the São Francisco River and with a strong presence of the Caatinga biome. The research hypothesis is that the settlement goes through a process of environmental degradation, reduction of native vegetation and that the Permanent Preservation Areas (APPs) are not in compliance with the Brazilian Forest Code. With this in mind, the following research aimed to: raise or use land cover in the Jacaré-Curituba irrigated perimeter and thus use subsidies for public policies to encourage sustainable development. The methodology was carried out based on the following processes: literature review; choice of a high resolution satellite image, Gaofen-2; image processing with remote sensing techniques in the QGis software; and subsequently, the following types of classification were performed: manual, unsupervised, supervised interactive and supervised using the Maximum Likelihood algorithm (MaxVer). As the non-manual notifications generated land use maps that were consumed according to their quality through the confusion matrix that extracted the Kappa coefficient and the global accuracy. Among them, the MaxVer classification obtained a higher Kappa 0.59. The land use and land cover maps obtained with manual classification and MaxVer were subjected to a cut that extracted the Permanent Protection Areas (APPs) of the settlement to assess the existence of conflicts in relation to what is recommended by the Forest Code (Law 12.651 / 2012). Then, it was found that about 50% of its territory is covered by native vegetation; as for the areas of APP, it was concluded that 30% are anthropized, that is, in conflict with legislation. From these results it was possible to indicate strategies for adapting the settlement to the Forest Code and promoting sustainability.